The Dynamics of Decoloniality in Theological Education: A Critique of the History of United Theological College (UTC) for Indigenous Clergy in Zimbabwe - Masvotore, Peter (Stellenbosch Theological Journal, 2022)
The consequences of colonialism and coloniality on indigenous social, political, and economic establishment are at present a grave concern. The call to decolonise theological education curricular, intellectual setting, and infrastructures has become the norm. This article posits a framework to evaluate nuances of missionary education at the United Theological College using Grosfoguel's conceptual lens of coloniality of knowledge. The article introduces the theoretical lens that undergirds this study and describes the aforesaid scope. The essay further presents an analysis of the endeavours of the United Theological College as an example of an ecumenical college in Zimbabwe. The aim of this article is to show how the United Theological College used education to racialize and how the indigenous people are put in hierarchies and how, in this process, of coloniality of knowledge, indigenous clergy were undermined. The argument for this article is that the economic, political, or social control of indigenous clergy could not have been complete or effective without mental control. In conclusion, the essay proposes how power structures and colonised knowledge systems could be decolonised.